Automated Search for Optimal Standard Sections - Ginsburg, S.; Kaaz, G. (Engineering Journal, 1985)
Microcomputers provide the engineer with practical tools for structural analysis and design. Beyond the obvious analysis, usually performed by using canned programs, there are many useful operations for which the microcomputer can be employed. This paper describes one such application, the search for minimum-weight cross sections. Done manually, this is a tedious job for the designer. Even when automated optimization is performed, the task of choosing a standard section still remains. An efficient search algorithm is described here, which can easily be adopted by practitioners, especially if they use BASIC for programming. The method is demonstrated by several examples where a minimum area is chosen from the table of W shapes in the AISC Manual of Steel Construction.